Men's eating disorders - A literature review - Anna Chmura; Patrycja Baciur; Katarzyna Skowrońska; Anna Karaś (Kazimierz Wielki University, 2022)
Introduction and purpose: Eating disorders belong to the group of mental diseases characterized by significant somatic complications and high mortality. There is a common opinion that these disorders mainly affect women. Such assumptions may result in limited knowledge of the diagnosis and treatment of an eating disorder in the male population. The aim of this study is to summarize the current knowledge about eating disorders among men, including binge eating disorder (BED), anorexia nervosa (AN) and bulimia nervosa (BN). Description of the state of knowledge: It turns out that the problem of eating disorders among the male sex is not so rare- it is estimated that approximately 10 million US men will experience an eating disorder at some point in their lives. The most common eating disorder among men appears to be binge eating disorder (BED). Men are also more likely to report binge eating than women. AN and BN occur much less frequently than BED in the male population. The symptoms of anorexia nervosa and bulimia nervosa may differ between men and women. More and more often we observe a development of a certain type of muscle dysmorphia among men, the so-called "reverse anorexia". Eating disorders carry a number of medical complications such as cardiac disorders, electrolyte disturbances, digestive problems and skeletal disturbances. Therapeutic interventions in the treatment of male eating disorders should take into account gender-specific problems. Conclusions: The real number of men suffering from eating disorders may be underestimated due to the neglect of the problem in the context of the male gender. It also results in poorly developed diagnostic and support schemes for men struggling with this problem. More research is needed on the topic of eating disorders in this group of patients as it will help to develop better diagnostic and therapeutic regimens adapted to the male gender.